2012
DOI: 10.1111/fwb.12007
|View full text |Cite
|
Sign up to set email alerts
|

Episodic acidification affects the breakdown and invertebrate colonisation of oak litter

Abstract: Summary 1. Although European streams are now recovering chemically from acidification, biological recovery is limited. One hypothesis is that continuing acid episodes restrict acid‐sensitive species in recovering locations either through direct toxicity or by affecting ecological processes. Here, we test this hypothesis by assessing the effects of episodic acid exposure on the breakdown and macroinvertebrate colonisation of oak (Quercus robur) litter. 2. Over 83 days, acid episodes of 4 days’ duration were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Shredders and predators were not affected. Our results are, thus, partly in accordance with Pye et al (2012), who reported that the proportion of predators, grazers and scrapers, but not the proportion of shredders, was negatively affected by acid episodes in streams. Grazers and scrapers and gatherers/collectors were the dominating EPT feeding groups in this stream and ecosystem functioning was, therefore, immediately affected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Shredders and predators were not affected. Our results are, thus, partly in accordance with Pye et al (2012), who reported that the proportion of predators, grazers and scrapers, but not the proportion of shredders, was negatively affected by acid episodes in streams. Grazers and scrapers and gatherers/collectors were the dominating EPT feeding groups in this stream and ecosystem functioning was, therefore, immediately affected.…”
Section: Discussionsupporting
confidence: 93%
“…Such events reorganize assemblages of macroinvertebrates by reducing populations of acid sensitive species or eliminating them (Merrett et al 1991;Lepori et al 2003b;Lepori & Ormerod 2005;Kowalik et al 2007). This may ultimately lead to reduced breakdown efficiency of organic litter (Dangles et al 2004) and retarded ecosystem functioning (Pye et al 2012). Assays of macroinvertebrates in response to AlS treatments in rivers in Norway are few and show contradicting results À from minor to severe perturbation of population sizes of acid sensitive taxa (Bongard 2005;Halvorsen & Heergaard 2007;Kjaerstad & Arnekleiv 2007;Eriksen et al 2009).…”
Section: Contact Tor Erik Eriksenmentioning
confidence: 99%
“…Hildrew & Ormerod, 1995). Furthermore, several ecosystem processes, such as decomposition (Hildrew et al, 1984;Chamier, 1987;Dangles et al, 2004;Simon et al, 2009;Pye et al, 2012), primary production (Mulholland et al, 1986;Niyogi et al, 2002) and bacterial production (Mulholland et al, 1992), are sensitive to mineral acid-ity and their rates seem generally reduced in acidic waters, possibly with ramifying indirect effects through freshwater food webs. Thus, the information available on the benthic secondary production of acidified streams also suggests that this is very low (Krueger & Waters, 1983;Griffith & Perry, 1994;Pretty et al, 2005;Stead et al, 2005;Woodward et al, 2005), probably partly as a result of the poor food quality of detritus in acidified streams (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters provide an overview of some of the most important water quality stressors affecting the aquatic biota, including nutrient pollution (Camargo and Alonso, 2006;Smallbone et al, 2016), acidity (Ormerod et al, 1987;Pye et al, 2012), and alterations in the overall ionic composition of water, as defined by water hardness and conductivity (Williams, 1987;Kefford et al, 2012). After the survey of biological indicators, we calculated the average width (m), depth (m) and current velocity (m/s) in each sampling site based on three values measured along transects set perpendicular to the water flow at 20 m intervals.…”
Section: Water and Physical Habitat Qualitymentioning
confidence: 99%